Penerapan Budaya 5S (Senyum, Salam, Sapa, Sopan Dan Santun) Dalam Menanamkan Kecerdasan Emosional - Fitri Adelia Rizqi; Jumari Jumari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education is the key to improving human intelligence, skills, and morals. In Indonesia, education aims to form a generation of believers and competent. The implementation of the 5S culture (Smile, Greeting, Greeting, Polite, Courteous) in schools, such as in MAN 4 Jombang, is important to instill emotional intelligence and good character. This study uses a qualitative approach with a case study method, collecting data through interviews, observations, and documentation. Informants include the Student Representative, BK Coordinator, teachers, and students. Data were analyzed using source triangulation to ensure validity. The 5S culture in MAN 4 Jombang aims to build a positive tradition despite facing challenges, where the support of teachers and parents is very important. The positive impact is seen in the increasingly polite attitudes of students, strengthening unity, and supporting character education. This culture also improves students' emotional intelligence, creates an inclusive and harmonious school environment, and encourages positive interactions and mutual respect.